Classification of Potential Risk Factors through HIRARC Method in Assessing Indoor Environment of Museums - Syahrun Neizam, Mohd Dzulkifli; Abd Halid, Abdullah; Lee, Yee Yong; Mohd Mahathir, Suhaimi Shamsuri; Zawawi, Daud (Penerbit UTHM, 2018)
Museums were established in Malaysia more than a hundred years ago. Since the year 2005, Malaysian government has discouraged constructing new purposely built museums in favour of refurbishing historic and old buildings to function as adaptive reused museums. Commonly due to insufficient ventilation, fully mechanically ventilated museums can pose critical indoor environmental issues that may lead to health hazards and risks among employees and visitors. Thus, the purpose of this study is to determine the potential risk factors within the museums based on indoor environmental criteria. This potential risk factors are resulted from the ‘Potential Risk Categories’, which have been developed by adopting the established Hazard Identification, Risks Assessment and Risk Control (HIRARC) Method. Based on the assessment of four main indoor environmental criteria in the Potential Risk Categories, it was discovered that 8 out of 24 museums are in the range of medium potential risk, while the rest of them are in the range of low potential risk. The ‘Potential Risk Categories’ is important for assessing indoor environment at the museums whereby the most critical risk could be assessed, and then suggestion could be provided to minimize the potential risk within the spaces inside the museums.